Punitive Agreed Payments for Non – Performance and Other Exorbitant Payments Having Close Nature in Lithuanian Contract Law - Budreckienė, Viktorija (Teisė, 2019)
[full article and abstract in Lithuanian; abstract in English]The author of article “Punitive agreed payments for non – performance and other exorbitant payments having close nature in Lithuanian contract law” analyses the notion of punitive amounts agreed for contractual non – performance (Lithuanian term “baudinės netesybos”) presented in case-law and legal doctrine. Also, as such amounts are forbidden in current Lithuanian contract law, the author examines related issues – cases of recognition of foreign arbitral tribunal decisions awarding agreed payments for contractual non – performance when debtor requests for non – recognition due to punitive (exorbitant) nature of the awarded amount arguing that they are contrary to the public policy. The examples of case-law presented in this article allow to reveal the issues related to the qualification of such amounts.
Keywords: contract law; agreed payments for contractual non-performance; arbitral tribunal decisions